Investigating the Effect of Basic Amino Acids and Glucosamine on the Solubility of Ibuprofen and Piroxicam - Hadi Valizadeh; Somayeh Mahdinloo; Negin Zakeri; Muhammad Sarfraz; Saeed Nezafat; Parvin Zakeri-Milani (Tabriz University of Medical Sciences, 2023)
Purpose: Poor aqueous solubility hampers the development of several compounds as pharmacological agents. Hence, preparing novel formulations with augmented absorption is a challenge in pharmaceutical industries. In this paper, we have examined the effect of basic amino acids including arginine (ARG), lysine (LYS), and glucosamine (GlucN) on the solubility of ibuprofen (IBU) and piroxicam (PXM) as drugs with limited solubility. We have also studied the effect of the dissolution media with the pH values 1.2 to 7.4. Methods: The saturation shake-flask method was used for solubility studies in the presence of amino acids. Briefly, buffer solutions containing different concentrations of amino acids were prepared. Then, an excess amount of each drug with these buffers was shaken to reach equilibrium. After 48 hours, the upper phase was separated, and solubility was calculated by reading their UV-Vis absorbance. Results: The results illustrated that amino acids increased solubility of both drugs with different ratios, which were pH and concentration-dependent. Solubility improved as the amount of amino acids went up, and this upward pattern was more robust with ARG than LYS. The presence of GlucN in citrate buffer significantly enhanced IBU solubility. The solubility of PXM in accompany of GlucN in water did not change significantly while in citrate buffer solubility enhanced specially at pH 6. Conclusion: Overall, GlucN in citrate buffer and ARG in phosphate buffer could be introduced as the most suitable media for IBU and PXM solubility improvement, respectively.